Drug screening to identify inhibitors of the structure-specific endonuclease ERCC1-XPF - McNeil, Ewan Murray (The University of Edinburgh, 2012)
Malignant melanoma results in 132,000 cases worldwide each year with an incidence rate that is increasing faster than for any other skin cancer. In the UK, cutaneous melanoma is the sixth most commonly diagnosed cancer and the second most common in young people aged 15-34 (excluding non-melanoma skin cancer). Furthermore, while less common than NMSC, malignant melanoma accounts for 4% of skin cancer cases and 74% of skin cancer-related deaths. Although early surgical removal of primary tumours is an effective treatment, patients that develop metastatic melanoma have a very poor prognosis (5 year survival rate is only 5%). Elevated expression of a number of DNA repair genes has been reported in primary melanomas that subsequently metastasised when compared to non-recurrent primary tumours. In addition, patients who do not respond to chemotherapy have elevated expression of DNA repair genes. One chemotherapeutic that is effective against a range of other cancers, but not melanoma is cisplatin. Elevated levels of the DNA repair protein ERCC1, which is needed to remove cisplatin-induced DNA damage, has been found to be an indicator of poor prognosis in ovarian and lung cancer. To test our hypothesis that elevated ERCC1 levels account for an increased resistance to cisplatin in melanoma, a xenograft experiment was performed. Our results show that ERCC1 proficient melanoma xenografts initially responded to cisplatin treatment however resistance soon followed. Tumours deficient in ERCC1 however could be cured after only two treatments of cisplatin, indicating a novel method to overcome chemoresistance in metastatic melanoma. The aim of the project was to identify novel compounds to improve therapy of melanoma. To achieve this, in collaboration with Dr Patton we performed a cell culture screen to identify compounds which display specificity against melanoma cell lines. In addition, we sought to identify compounds which would overcome cisplatin resistance. We identified a series of nitrofuran compounds which are potent against melanoma and neuroblastoma cell lines and enhanced the toxicity of cisplatin through an ERCC1 independent pathway. In addition, we showed that melanin pigmentation is protective against nitrofuran toxicity. We have proposed the structure specific endonuclease, ERCC1-XPF, as a drug target to overcome chemoresistance. We collaborated with Professor Walkinshaw to perform an in silico screen for protein-protein interaction inhibitors to disrupt the obligate dimerization between ERCC1 and XPF. In addition we directly inhibited the endonuclease activity by developing XPF endonuclease domain inhibitors and utilised a range of biochemical, molecular biology and cell culture assays to validate ERCC1-XPF inhibitors. Furthermore, we developed an in vitro endonuclease assay for ERCC1-XPF, FEN1 and DNase1 and utilised these to demonstrate compound specificity of our validated ERCC1-XPF inhibitors. In collaboration with MRC Technology we utilised the ERCC1-XPF endonuclease assay to perform a high throughput screen. We characterised hit compounds to demonstrate physical binding and in vitro specificity for ERCC1-XPF. In conclusion, we have discovered new compounds which may prove beneficial for the treatment of malignant melanoma.
Keywords: chemotherapy; melanoma